A new Haplidia Hope, 1837 (Coleoptera: Scarabaeidae: Melolonthinae) from the coast of south-western Turkey - Uliana, Marco; Ersoy, Doğan Erhan (Zootaxa, 2024)
A new species of Haplidia is described from the coastal area of Antalya, south western Turkey. Based on the peculiar morphology of paramera Haplidia fausta, new species, belongs to Baraud’s group 3, and is well distinct from all other species belonging to the same group for several traits of both external morphology and paramera. The only locality of observation is an area with sandy soil, covered by loose grassy vegetation and sparse bushes and pines stands at a few hundred meters from the shoreline.